PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA TENAGA KETEKNISIAN MEDIS DI RUMAH SAKIT UMUM DAERAH (RSUD) CIAWI KABUPATEN BOGOR - Krisnawati, Fransiska; Purnomo, Hadi; Silitonga, Witler Slamat Halomoan (Kompetensi (Competence : Journal of Management Studies), 2025)
ABSTRAKThis study was motivated by the crucial role of medical technicians in supporting the effectiveness of hospital health services. Competence and motivation are considered key factors determining employee performance, yet empirical studies focusing specifically on medical technicians remain limited. The purpose of this research was to analyze the influence of competence and motivation on the performance of medical technicians at RSUD Ciawi, Bogor Regency. The study employed a quantitative approach using questionnaires distributed to 36 respondents, and multiple linear regression analysis with SPSS. The results revealed that competence and motivation had a positive and significant effect, both partially and simultaneously, on performance, with a contribution of 96.7%. However, although competence and motivation were categorized as high, performance remained at a moderate level, indicating a gap between potential and actual outcomes. The study concludes that improving competence and motivation must be supported by organizational factors such as leadership, reward systems, and collaborative work culture. The recommendation highlights the need for continuous human resource development strategies and organizational strengthening to optimize medical technicians’ performance.Keyword :